Development of the multimodal text design training model for science teachers of gifted students: an educational design research - Ayık, Zekai (My University, 2021)
Meeting the pedagogical needs of gifted students in science classroom requires specific pedagogical strategies and the competencies of teachers. In gifted science classroom, this competency includes designing didactic texts which foster meaning making (internalized learning product) of content and creativity in externalized learning products. Informed by multimodality and social semiotics, this study aims to develop a professional development model (intervention) that will develop multimodal didactic science text design competencies of science teachers of gifted of gifted students. The multimodal didactic science texts are expected to support (1) meaning-making of science content and (2) creativity in learning products. The intervention model has been developed within educational design research methodology. Six experienced in-service science teachers who work in schools of gifted students (BILSEM). Data is continuously gathered by interview data and participant’s multimodal text designs. Data analysis was done both qualitatively and quantitatively. The developmental progress of participants’ text design competency was the monitor of the development of the training program. The development of intervention model involves a preliminary phase, development phase (prototyping), and evaluation phase. The developed training model consists of design principles and two hypothetical learning trajectories that have their own learning goals, content, learning activities, and assessment tools. Learning activities in a HLT involve awareness, recognize, overt instruction, design, feedback, and re-design activities. In the end of the study, it was observed that the training model for multimodal didactic science texts design significantly improved the design skills of the participant teachers in the expected direction and the program was developed for future implications.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Gifted education; Multimodality; Didactic texts; Science education; Educational design research